Effects of Harvest and Fertilization Frequency on Protein Yield and Extractability From Flood-Tolerant Perennial Grasses Cultivated on a fen Peatland - Nielsen, Claudia Kalla; Stødkilde, Lene; Jørgensen, Uffe; Lærke, Poul Erik (Frontiers in Environmental Science, 2021)
Paludiculture, and in particular the cultivation of perennial grasses as biomass feedstock for green biorefineries, may be an economic and environmentally sustainable option for agricultural peatlands in temperate regions. However, the optimal biomass quality for protein extraction from flood-tolerant grasses is largely unknown. The aim of this study was to define the combined effect of harvest and fertilization frequency, with one to five annual cuts, on protein yield and extractability for the grasses tall fescue (TF) and reed canary grass (RCG), cultivated on an agricultural fen peatland in Denmark. The content of protein fractions was determined according to the Cornell Net Carbohydrate and Protein System (CNCPS). We assessed protein extractability by lab-scale biorefinery techniques using a screw-press followed by acid precipitation of true protein. The two methods were compared to correlate potential extractable protein yields with actual biorefinery outputs. We found the highest annual biomass and crude protein (CP) yields in the two cut treatments, with 13.4 and 15.6 t dry matter (DM) ha-1 yr-1, containing 2.9 - 3.4 t CP ha-1 yr-1 for TF and RCG, respectively. The highest neutral-extractable (fractions B1 and B2) true protein yields of 1.1 and 1.5 t ha-1 yr-1 were found in the two cut treatments, representing 39 % (TF) - 45 % (RCG) of total CP. Using biorefining techniques, we were able to precipitate up to 2.2 t DM ha-1 yr-1 of protein concentrate, containing up to 39 % CP. Significant correlations between methods were found, with a distinct relationship between CNCPS fractions B1 + B2 and CP yield of the protein concentrate, indicating the suitability of the CNCPS as an indicator for extractable protein yields. Biomass and CP yields were not significantly improved beyond two annual cuts. However, timing and harvest frequencies significantly affected plant maturity and consequently extractable CP contents and protein concentrate yields. We conclude that TF and RCG are promising feedstocks for green biorefineries due to high biomass, extractable CP, and protein concentrate yields, and highlight the potential of flood-tolerant grasses, cultivated on wet agricultural peatlands, for an enhanced valorisation beyond the common utilisation for bioenergy.